2021
DOI: 10.1128/msphere.00637-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic and Transcriptomic Analysis of Naegleria fowleri Clinical and Environmental Isolates

Abstract: N. fowleri , the only known Naegleria species to infect humans, causes fatal brain disease. PAM cases from 1965 to 2016 showed <20 cases per year globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…However, the 12S rRNA and ITS1 sequences showed disagreement in the genotype between each other ( Figures 3 , 5 ). Interestingly, this discrepancy was also observed in the isolate V1005 from the PAM patient in Australia on both mitochondrial 12S rRNA and nuclear ITS1 genes ( Joseph et al, 2021 ). It was previously reported that genotyping based on 12S rRNA and ITS1 was consistent between the two loci ( Zhou et al., 2003 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, the 12S rRNA and ITS1 sequences showed disagreement in the genotype between each other ( Figures 3 , 5 ). Interestingly, this discrepancy was also observed in the isolate V1005 from the PAM patient in Australia on both mitochondrial 12S rRNA and nuclear ITS1 genes ( Joseph et al, 2021 ). It was previously reported that genotyping based on 12S rRNA and ITS1 was consistent between the two loci ( Zhou et al., 2003 ).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, we wanted to compare the drug susceptibilities of the clinical isolates with their genotypes. There is published internal transcribed spacer (ITS) genotype information, determined based upon the techniques described by Zhou et al, for all of the isolates except Nf69 ( 39 , 40 ). After obtaining Sanger sequencing results for the PCR products for Nf69, we trimmed off poor-quality base pairs and aligned the sequences obtained for the forward primer sequencing samples as well as the reverse primer sequencing samples to attain a 446-bp sequence.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Joseph et al sequenced the genomes for each of the isolates tested in our study, and we downloaded and processed these data in order to perform the aforementioned genotyping technique and compare the genotype results attained with the system created by De Jonckheere with those reported based on the work of Zhou et al ( 39 41 ). Using Geneious Prime software, we pairwise aligned the forward and reverse reads for each clinical isolate and then mapped these to each of the 2 ITS primers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naegleria fowleri ( N. fowleri ) is a free-living amoeba that can infect humans through the nasal mucosa and cause central nervous system diseases, such as primary amoebic meningoencephalitis (PAM) ( 60 , 61 ). Because NETs may be an important factor in the fixing and killing of invading microorganisms, the study of the role of NETs in central nervous system diseases caused by N. fowleri will help us to better understand the relevant mechanisms and regulatory pathways of parasites involved in the occurrence and development of diseases.…”
Section: Phylum Sarcomastigophora Class Loboseamentioning
confidence: 99%